A lightweight and privacy-preserving mutual authentication scheme for wearable devices assisted by cloud server. (October 2017) - Wu, Fan; Li, Xiong; Xu, Lili; Kumari, Saru; Karuppiah, Marimuthu; Shen, Jian
Abstract: As a popular technology for Internet of Things (IoT), wearable devices are accepted widely by people. Classic wearable devices including glasses and watches collect wearers' information which is usually private. Often, a single wearable device is not enough to see the data of the user and a mobile terminal such as a smart phone is used to match the wearable device. Also, the gathered data are often stored in the remote cloud server. Security issues become the emergent tasks and they have not been solved perfectly. Until now, there are weaknesses in traditional authentication ways, and such ways are not fit for the communication. Therefore, we propose a new and lightweight authentication scheme for wearable devices with help of cloud server. This scheme reaches mutual authentication and keeps anonymous for the devices. Compared to two recent schemes of the similar kind, ours is more secure and applicable.